Portraying the English Morphological Development of Indonesian-English Interlanguage Learners - Rudi Suherman; Lia Maulia Indrayani; Ekaning Krisnawati (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
The study intends to see the interlanguage morphological structure observed in communicative tasks of ten Indonesian learners of English as a Foreign Language.  To achieve this purpose, Qualitative method with quantified data is employed in this study embracing the cross-sectional approach. The data are taken from the utterances produced by 10 (ten) L2 learners who performed three different communicative tasks; semi-structure interviews, 5 picture descriptions, 2 spot differences. The researcher found 356 English morphological structures produced by the learners, and 66 of them are analysed as data samples the analysis is started by profiling their morphological acquisition. It helps the researcher to provide a vivid picture of their English morphological development stage. After analysing the data, the result shows that the English morphological structures produced by the L2 learners in this study are divided into three types:  Suppliance, non - suppliance and over – suppliance structures. Suppliance structure refers to structure that is received by grammatical rules in standard English. Meanwhile, the other two types of structure refer to idiosyncratic structures as an innate characteristic of interlanguage morphology. Besides, English morphological development stage is compatible with the Processability Theory (PT). The learners who have acquired higher morphological structure also have already acquired lower morphological structure.